2020
DOI: 10.1093/occmed/kqaa060
|View full text |Cite
|
Sign up to set email alerts
|

Physical training in the fire station and firefighters’ cardiovascular health

Abstract: Background Few fire departments in Québec have a diversified health promotion programme. Yet, many allow firefighters to physically train during working hours. Aims To compare the weekly physical activity (PA) level and cardiovascular health indicators of firefighters who physically train on duty to those who do not. Methods Participants underwent a cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…However, regular exercise when on duty did reduce the incidence of injuries outside of the workplace. High workload when on duty, compounded by exercise or training workload and inadequate recovery possibly produced a burdensome triad that reduced musculoskeletal health and contributed to the increased incidence of duty-related injury [ 78 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, regular exercise when on duty did reduce the incidence of injuries outside of the workplace. High workload when on duty, compounded by exercise or training workload and inadequate recovery possibly produced a burdensome triad that reduced musculoskeletal health and contributed to the increased incidence of duty-related injury [ 78 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Damacena et al 64 reported that central obesity was more likely in firefighters who had low PA levels. Gendron et al 65 reported that there was a significant difference in WC and obesity in firefighters who trained while on duty than those who did not. Although firefighters remain active while on duty, because they are not exercising at a moderate-to-high-intensity they do not receive the additional benefits of increased energy expenditure associated with fat loss.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that blood pressure increased throughout the study period (Lan et al 2021 ). For this reason, some authors indicated the need for the implementation of physical activity and nutrition outreach programs, which would increase physical activity in this group and reduce the incidence of overweight and obesity (Martin et al 2019 ; Barry et al 2020 ; Gendron et al 2020 ).…”
Section: Airway and Systemic Inflammation In Firefightersmentioning
confidence: 99%